Inorganic-organic photodiodes based on polyaniline doped boric acid and polyaniline doped boric acid:nickel(II) phthalocyanine composite - Yakuphanoğlu, Fahrettin; Kandaz, Mehmet; Senkal, B. Filiz (Elsevier Science Sa, 2009)
The electronic and photovoltaic properties of hybrid organic photodiodes based on n-Si/boric acid doped polyaniline (PANIB) and n-Si/2,3,7,8,12,13,17,18-octakis(2'-aminophenylsulfanyl)-substituted-nickel(II) phthalocyanine: boric acid doped polyaniline (PANIB-PC) composite have been investigated. The current-voltage characteristics of the n-Si/PANIB and n-Si/PANIB-PC diodes were analyzed under dark and illumination conditions. The open circuit voltage, V-oc and short circuit current, I-sc values for the n-Si/PANIB and n-Si/PANIB-PC diodes under 105 mW/cm(2) were respectively found to be 0.280 V, 6.19 nA and 0.304 V, 0.091 nA. The fabricated inorganic/organic devices can be used as an optical sensor for optoelectronic applications. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Photodiode; Organic semiconductor; Boric acid doped polyaniline